DIVERSITY, ABUNDANCE AND COMPOSITION OF LARGE FRESHWATER PRAWN SPECIES IN THE GANGA RIVER SYSTEM - SUDAY PRASAD; D. R. KANAUJIA; A. K. PATRA (The Bioscan, 2012)
The composition and temporal distribution of large freshwater prawn species in the Ganga river around Patna were studied during January 2000 - December 2001 and two larger Macrobrachium species were recorded. The species composed of Macrobrachium malcolmsonii, M. gangeticum and M. lamarrei; among them, the small species M. lamarrei was the dominant one throughout the year followed by larger ones M. gangeticum and M. malcolmsonii. The catch of M. gangeticum and M. malcolmsonii was restricted and their availability was found to be during May to October in middle stretch of the river Ganga around Patna in both the years. The species M. gangeticum possess prominently curved rostrum with highly convex elevated dorsal crest, whereas in M. malcolmsonii, the rostrum is slightly elevated and projecting upto antennular peduncles. The catch composition was recorded maximum 70.89 % during monsoon and rest 29.11 % in summer during first year. During second year maximum 72.22% recorded in monsoon and minimum 27.78% in summer. The percentage composition of two larger species M. gangeticum and M. malcolmsonii ranged from 75 to 90 % and 6.1-18.0 % respectively during two years in different months and season.